Characterization and preventability of adverse drug events as cause of emergency department visits: a prospective 1-year observational study - Ivan Lo Giudice; Eleonora Mocciaro; Claudia Giardina; Maria Antonietta Barbieri; Giuseppe Cicala; Maria Gioffrè-Florio; Giuseppe Carpinteri; Aulo Di Grande; Edoardo Spina; Vincenzo Arcoraci; Paola Maria Cutroneo (BMC, 2019)
Abstract Background Adverse drug events (ADEs) are a significant cause of emergency department (ED) visits, with a major impact on healthcare resource utilization. A multicentre observational study, aimed to describe frequency, seriousness and preventability of ADEs reported in four EDs, was performed in Sicily (Italy) over a 1-year period. Methods Two trained monitors for each ED supported clinicians in identifying ADEs of patients admitted to EDs between June 1st, 2013 and May 31st, 2014 through a systematic interview of patients or their caregivers and with an additional record review. A research team analyzed each case of suspected ADE, to make a causality assessment applying the Naranjo algorithm and a preventability assessment using Schumock and Thornton criteria. Absolute and percentage frequencies with 95% confidence interval (CI) and medians with interquartile ranges (IQR) were estimated. Logistic regression models were used to evaluate independent predictors of serious and certainly preventable ADEs. Results Out of 16,963 ED visits, 575 (3.4%) were associated to ADEs, of which 15.1% resulted in hospitalization. ADEs were classified as probable in 45.9%, possible in 51.7% and definite in 2.4% of the cases. Moreover, ADEs were considered certainly preventable in 12.3%, probably preventable in 58.4%, and not preventable in 29.2% of the cases. Polytherapy influenced the risk to experience a serious, as well as a certainly preventable ADE. Whilst, older age resulted an independent predictor only of serious events. The most common implicated drug classes were antibiotics (34.4%) and anti-inflammatory drugs (22.6%). ADEs due to psycholeptics and antiepileptics resulted preventable in 62.7 and 54.5% of the cases, respectively. Allergic reactions (64%) were the most frequent cause of ADE-related ED visits, followed by neurological effects (10.2%) that resulted preventable in 1.9 and 37.3% of the cases, respectively. Conclusion ADEs are a frequent cause of ED visits. The commonly used antibiotics and anti-inflammatory drugs should be carefully managed, as they are widely involved in mild to severe ADEs. Polytherapy is associated with the occurrence of serious, as well as certainly preventable ADEs, while older age only with serious events. A greater sensitivity to drug monitoring programs among health professionals is needed.